Flexural Properties, Impact Strength, and Hardness of Nanodiamond-Modified PMMA Denture Base Resin - Shaimaa M. Fouda; Mohammed M. Gad; Passent Ellakany; Maram A. Al Ghamdi; Soban Q. Khan; Sultan Akhtar; Mohamed S. Ali; Fahad A. Al-Harbi (International Journal of Biomaterials)
Purpose. Investigate the effect of low nanodiamond (ND) addition and autoclave polymerization on the flexural strength, impact strength, and hardness of polymethylmethacrylate (PMMA) denture base. Methods. A total of 240 heat polymerized PMMA were fabricated with low ND concentrations of 0.1%, 0.25%, and 0.5%, and unmodified as control. The specimens were divided equally into group I: conventionally polymerized PMMA by water bath and group II: polymerized by the autoclave. The impact strength, flexural strength, and elastic modulus were tested using the Charpy-type impact-testing machine and three-point bending test, respectively. A scanning electron microscope (SEM) was used to analyze the fractured surfaces. Surface hardness was measured by a hardness tester with a Vickers diamond. The bonding and interaction between the PMMA and ND particles were analyzed by the Fourier-transform infrared (FTIR) spectroscope. ANOVA and post hoc Tukey test were used for data analysis (α = 0.05). Results. ND addition significantly increased the flexural strength of groups I and II (p<0.001, p=0.003); it was highest (128.8 MPa) at 0.25% ND concentration for group I and at 0.1% for group II. Elastic modulus increased at 0.1% ND for both groups (p=0.004, p=0.373), but the increase was statistically significant for group I only. Impact strength showed no significant change with the addition of ND in groups I and II (p=0.227, p=0.273), as well as surface hardness in group I (p=0.143). Hardness decreased significantly with 0.25%ND in group II. Conclusion. The addition of ND at low concentration increased the elastic modulus and flexural strength of conventionally and autoclave polymerized denture base resin. Autoclave polymerization significantly increased the flexural strength, impact strength, and hardness of unmodified PMMA and hardness of 0.5% ND group.